Kontribusi Lazismu dalam Membangun Kemandirian Ekonomi Masyarakat Miskin Melalui Bantuan Modal bagi UMKM - Marpaung, Durahman; Bakti, Surya (CV. IRA PUBLISHING, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in Indonesia's economy, contributing to economic growth, labor absorption, and poverty reduction. However, challenges such as limited access to credit and concerns about rejected credit applications often hinder the development of MSMEs. In Asahan Regency, the potential of MSMEs to improve regional economic welfare is huge thanks to abundant natural resources and local products. This article evaluates the impact of the assistance program organized by Lazismu on the economic independence of the poor through the development of culinary MSMEs in Kisaran. This study uses a comprehensive analysis method to assess how Lazismu's intervention affects aspects such as income, business capacity, and competitiveness of culinary MSMEs. The results of this study are expected to identify the key factors for the success of the program and provide recommendations for the development of economic empowerment programs in the future. The findings of this study also aim to contribute to the academic literature on the effectiveness of economic empowerment programs and provide guidance for policymakers and practitioners in the development of MSMEs.